The freedom of man in the works of Marx and Engels. - Mullowney, Mary Thaddeus. (University of Ottawa (Canada), 1964)
According to the Thomistic concept of freedom, human freedom has its source in freedom of choice, which may be used for the development of man's spiritual and temporal potentialities in keeping with his eternal destiny. Man, who always seeks some good, must seek the perfect good. This is the only necessity or determination that affects man's will. Towards the middle of the nineteenth century, Karl Marx became concerned about the lack of freedom for the worker in the increasingly industrialized society that resulted from the Industrial Revolution. With the collaboration of Frederick Engels, he took upon himself the task of improving the lot of the toiling masses. This was to be accomplished by a combination of economic laws, materialism, and the dialectic, in such a way as to supply a complete way of life for man.
Keywords: Philosophy.